Historical blocking: CN 2019-06-08 (China) - Voidly (2019)
CRITICAL severity censorship detected in China. Confidence: 82%. Data sourced from ooni-historical-backfill.
Censorship Incident ID: CN-2019-0007
Keywords: censorship; CN; censorship; critical